The Role of the Aisyiyah Tanggulangin Branch in Overcoming the Problems of Children and Women - Faiqotul Maghfiroh; Lindania Febriyanti; Kusuma Dewi P.A.M; Nurul Asnah; Anjalita Nanda Budiarti (Proceedings of The ICECRS, 2020)
This study aims to determine the important role of Aisyiyah branch of Tanggulangin in Putat area in overcoming the problems of children and women. All data is taken from the result of interviews with administrators Aisyiyah Putat. Research results obtained from interview that Aisyiyah putat area has many good programs including : (1) routine recitation at the level of Aisyiyah branch leadership is held every week, (2) at the level of Aisyiyah branch leadership held every two weeks, (3) at the level Aisyiyah regional leader are held once every one mont which is carried out in Aisyiyah vranch leadership in rotation, (4) the social sector provides compensation, (5) the education sector establishes kindergarten and TPQ, and (6) the tabligh field holds recitation.